Salidroside enhances 5-fluorouracil sensitivity against hepatocellular carcinoma via YIPF5-induced mitophagy - Sun, Sumin; Hu, Haili; Li, Feiyu; Huan, Sheng; Chen, Long; Chen, Jiahui; Sun, Peihua; Dong, Xiaoqing (Frontiers in Pharmacology, 2025)
Hepatocellular carcinoma (HCC) is a major medical challenge due to its high incidence and poor prognosis. 5-Fluorouracil (5-FU), although extensively studied in the treatment of HCC and other solid tumors, has limited application as a first-line therapy for HCC due to its resistance and significant inter-patient variability. To address these issues, researchers have explored drug repurposing. One of our key findings in this endeavour was the potent anti-HCC effect of the natural product Salidroside (Sal) when co-administered with 5-FU. Sal was found to inhibit mitosis and promote cellular senescence in HCC cells via a mechanism distinct from 5-FU, specifically by inducing excessive mitophagy that led to cellular mitochondrial dysfunction. Importantly, YIPF5 was confirmed as a potential molecular target of Sal. This natural product modulated YIPF5-induced mitophagy and influenced both mitosis and senescence in HCC cells. The combination of Sal and 5-FU demonstrated significant therapeutic effects in a mouse HCC model. In conclusion, our study was not only in line with the innovative strategy of drug repurposing, but also important for drug design and natural product screening targeting the relevant pathways.